AD, Volume 47, n° 2, 2022 - Full Issue - journal system, journal system (Africa Development, 2022)
Contents Text of the Inaugural Thandika Mkandawire Annual Memorial Lecture On Resuscitating the Aborted National Project: A Retrospective and Prospective View (Notes from my last conversation with Thandika Mkandawire) Fantu Cheru ...................................... 1 Selected Papers from the 2019 CODESRIA Demoractic Governance Institute Digital Technologies and Election Management in Africa’s Democratisation Process: More Technocratic than Democratic? Okechukwu Obinna Ibeanu....................................15 L’illusion du e-voting dans les organisations syndicales en Côte d’Ivoire : entre légitimité et défis démocratiques Yao Adoman Francis Kouadio.................................41 Droit d’accès à l’internet et ordre public électoral en Afrique : la crédibilisation institutionnelle au Congo-Kinshasa à l’épreuve de la surveillance e-citoyenne Jacques Kambale Bira’Mbovote............................61 Machine à voter et résistance politique à l’élection présidentielle 2018 en RDC Antomella Kornégie Atipo..................................85 The ‘#tag Generation’: Social Media and Youth Participation in the 2019 General Election in Nigeria Oluwasola Festus Obisesan.............................107 “Open the Servers”: The Implications of Electoral Technology to Kenya’s Democratisation Process Joyce Omwoha...........................................147 The Role of ICT in Curtailing Electoral Fraud and Violence in Nigeria: A Study of the 2019 General Election in Lagos State Ifeanyi U. Chukwuma.................................161 Digital Technologies and Election Management in Zimbabwe: Pseudo-democratic Transition and Contorted Delirium? Torque Mude...........................................179 Interrogating the Cost of Digital Technology and Trust in Elections in Africa: The Nigerian Perspective Felicia Osondu Okwueze........................199